2007
DOI: 10.1007/s12011-007-0041-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Concentrations in Cystic Fibrosis Patients Aged Above 4 Years: A Cross-sectional Evaluation

Abstract: Aim: Assess the risk of zinc (Zn) deficiency in the older cystic fibrosis (CF) population. Method:Cross sectional investigation of all CF patients above the age of 4 followed at the Ghent university centre between 2002 and 2003. Data on age, weight and height z-score, pancreatic and pulmonary functions, chronic pseudomonas infection and CF transmembrane conductance regulator (CFTR) mutations were collected. Serum Zn, vitamin A, E, retinol binding protein (RBP), albumin, sedimentation rate, total IgG and choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Further striking clinical features were loss of appetite and stunted growth. The serum Zn concentrations in our CF patients are rather low when compared to the literature [16] but also our healthy control population had the same low serum Zn concentrations [21] . As shown in our recent report on this subject, only the patients with pancreatic insufficiency had decreased serum Zn concentrations below 65 g/dl, the lower 'normal' (p = 2.5) serum Zn value of the NHANES II study [16,22] .…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…Further striking clinical features were loss of appetite and stunted growth. The serum Zn concentrations in our CF patients are rather low when compared to the literature [16] but also our healthy control population had the same low serum Zn concentrations [21] . As shown in our recent report on this subject, only the patients with pancreatic insufficiency had decreased serum Zn concentrations below 65 g/dl, the lower 'normal' (p = 2.5) serum Zn value of the NHANES II study [16,22] .…”
Section: Discussionsupporting
confidence: 48%
“…Comparisons were made with a not supplemented control CF population with higher levels of serum Zn [16] and a randomly selected age-matched control CF subgroup.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no such relation was found in the study on 36 children with cystic fibrosis by Van Biervliet et al 14 Another study reported that serum zinc levels in children with cystic fibrosis were similar to those of normal controls but that children with lower serum zinc levels had significantly worse results on the pulmonary function tests. 15 An increase has been observed in the sputum zinc levels in pulmonary exacerbations, and a decrease has been observed in the levels after treatment in bronchiectasis (cystic fibrosis and non-cystic fibrosis bron- chiectasis); however, the significance of this remains unclear. 16 Tinley et al 17 observed an interaction between the serum zinc and vitamin levels.…”
Section: Discussionmentioning
confidence: 99%